1979
DOI: 10.1021/jo01334a025
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of ene reactions of glyoxylate esters

Abstract: IV-Methyl-lV-[4-(IV,lV-dimethylamino)-2-methylbenzyl]-JV,,jV '-dimethyl-4,4,-diamino-2,2,-dimethyldiphenylmethane (19): NMR (CC14) 2.11 (s, 6 H, ArCH3), 2.17 (s, 3 H, ArCHg), 2.74 (s, 3 H, NCH3), 2.77, 2.79 (2 s, 12 H, NCH3), 3.56 (s, 2 H, ArCH2Ar), 4.17 (s, 2 H, NCH2Ar), 6.10-6.90 (m, 9 H, aromatic protons); IR (film) 3000-2800 (s), 1620 (vs), 1515 (vs), 1480 (m), 1450 (m), 1350 (s), 805 (s), 780 (w), 760 (w), 705 (vw), 695 (vw) cm'1; mol wt of C28H37N3, 415.62; mass spectrum (70 eV),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The previous edition 1 included the determination of endo/exo stereochemistry of the thermal and FeCl 3 -catalyzed ene reactions of methyl glyoxylate with various alkenes, 46 and Whitesell's development of asymmetric ene reactions of glyoxylate esters using 8-phenylmenthol and trans-2-phenylcyclohexanol as chiral auxiliaries. 47 Applications 48 of the latter reaction in total synthesis include the SnCl 4 -catalyzed reaction of diene 31 with trans-2-phenylcyclohexyl glyoxylate (32) to give 33 in 81% yield, which was elaborated to (-)-specionin (34) symmetry and controls the stereochemistry at both centers.…”
Section: Glyoxylate Estersmentioning
confidence: 99%
“…The previous edition 1 included the determination of endo/exo stereochemistry of the thermal and FeCl 3 -catalyzed ene reactions of methyl glyoxylate with various alkenes, 46 and Whitesell's development of asymmetric ene reactions of glyoxylate esters using 8-phenylmenthol and trans-2-phenylcyclohexanol as chiral auxiliaries. 47 Applications 48 of the latter reaction in total synthesis include the SnCl 4 -catalyzed reaction of diene 31 with trans-2-phenylcyclohexyl glyoxylate (32) to give 33 in 81% yield, which was elaborated to (-)-specionin (34) symmetry and controls the stereochemistry at both centers.…”
Section: Glyoxylate Estersmentioning
confidence: 99%
“…With cyclohexene and FeCl 3 catalyst, a 4.4:1 mixture of endo/exo adduct is obtained. 12 Extensive cis-trans isomerization of the double bond in the substrate under the reaction conditions, as well as contamination of halogen adducts in the products, point to a stepwise cationic mechanism for the Lewis acid-catalyzed glyoxylate-ene reactions. 13 The reaction course of vinylsilane with glyoxylate, on the other hand, depends on the geometry of the vinylsilane and the Lewis acid employed.…”
Section: Original Commentarymentioning
confidence: 99%
“…40 The configuration of the new center in the adducts was (S) with SnC4, BF3 and TiCl4 and (R) with AICI3. In marked contrast to these results, Whitesell found that excellent asymmetric induction is obtained with 8-phenylmenthyl and trans-2phenylcyclohexyl glyoxylate esters.…”
Section: Glyoxylate Estersmentioning
confidence: 99%